Perilaku Pengelolaan Keuangan Mahasiswa Ditinjau Dari Literasi Keuangan Dan Pemahaman Ajaran Trikon - Dewi Kusuma Wardani; Fiki Bela Oktavia (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The low financial management ability among students is an important concern, especially in the digital era which offers ease of transaction but also has a high risk of consumptive behavior. This study aims to analyze the influence of financial literacy and understanding of the teachings of Trikon on student financial management behavior. The research approach used was quantitative associative with purposive sampling techniques on 125 students in Yogyakarta. The data were analyzed using multiple linear regression. The results of the study show that both financial literacy and understanding of Trikon teachings have a positive effect on financial management behavior. These findings affirm the importance of financial education that combines financial understanding with cultural values and national character.